Development of a device for measuring force and timing in a K2 kayak during flatwater paddling - Klitgaard, K. K. (Aalborg University, 2017)
The aim of the study was to develop a device which could measure leg kicking forces and timing between paddlers in a flatwater sprint K2 kayak. The two footrests of a K2 were each fitted with two load cells mounted on an aluminum plate which was attached to each footrest. A Shimmer3 bridge amplifier was used as an analog amplifier and as a data acquisition system. Three pilot tests with different set-ups were conducted with two national elite male paddlers. The devices were calibrated by loading each footrest witha series of weights placed on the middle of the footrest. Further, the footrest measuring devices were tested for validity by placing a fixed load on different points of the footrest. A strong linearity of both footrests measuring devices was found (r2 = 0.99948 and 0.99684) when force was applied on the middle of the footrest. However, the validity test showed that the force output had a large percentage of deviation fromthe fixed load dependent on the position of the load. Thus, the measured force might deviate from the actual force. The tests did, however, show that the footrest measuring devices were able to record data without drifting in time, thereby enabling analysis of timing. Wireless data was not obtained due to a short rangeof the Bluetooth connection. A training tool prototype which enables measurement of the timing in the legkick both in K1 and crew boats (K2 and K4) has been developed based on the findings of the study.